2021
DOI: 10.3390/f12040505
|View full text |Cite
|
Sign up to set email alerts
|

Niche Selection by Soil Bacterial Community of Disturbed Subalpine Forests in Western Sichuan

Abstract: Soil bacterial microbial communities are important in the ecosystem function and succession of forests. Using high-throughput 16S rRNA gene sequencing and relative importance for linear regression, we explored how the structures of soil bacterial community were influenced by the environmental factors and restoration succession of secondary forests in the Miyaluo Mountains of western Sichuan, China. Using a space-for-time approach, field measurements and sampling were conducted in four stands at different stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Microorganisms in soil are crucial for plant development and play important roles in soil ecology and regeneration. They are essential components of soil ecology and important mechanisms of soil regeneration. However, culture-independent approaches have revealed that the microbial diversity levels in soil and the rhizosphere are often greatly underestimated. Furthermore, the driving forces behind changes in microbial diversity remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms in soil are crucial for plant development and play important roles in soil ecology and regeneration. They are essential components of soil ecology and important mechanisms of soil regeneration. However, culture-independent approaches have revealed that the microbial diversity levels in soil and the rhizosphere are often greatly underestimated. Furthermore, the driving forces behind changes in microbial diversity remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms in the soil play significant roles in plant development(Sheng et al, 2021; Sun et al, 2021; Warmink and van Elsas, 2009; Zhao et al, 2014). They are an essential component of soil ecology and serve as an important mechanism for soil regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy-metal contamination has been implicated frequently in altering soil microbial community structure by reducing soil nutrient. Various factors, like soil pH, available phosphorous, and hydrolyzed nitrogen, may influence soil bacterial diversity ( Li H. et al, 2021 ; Sheng et al, 2021 ). Moreover, it has also been documented that microbes show potential capacity in the remediation of heavy metals pollution in soil ( Chen et al, 2020 ; Xie et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%